Payment and Transaction Risk Management at Coffeeshop X Using NIST 800-30 Framework - Noven Wirlando Marbun; Faris Asasul Iz; Muhammad Ramadhan; Lorrida Jein Herlina Kogoya; Lazuardi Fahreza Nugraha; Ucu Nugraha (LP2M Universitas Widyatama, 2023)
Information technology enables efficient and effective completion of activities, saving both time and energy. However, this convenience comes with inherent risks that need to be managed to prevent severe consequences such as information leaks, financial losses, and disruptions to business processes. This research focuses on implementing the NIST 800-30 framework as a risk management framework for Coffeeshop X. The objective is to provide concrete steps and recommendations for mitigating potential risks. The analysis identifies several risks that could threaten the business continuity of Coffeeshop X, including natural disasters, operating system vulnerabilities, physical security breaches, and damage to software and hardware. By applying the NIST 800-30 framework, the research highlights specific control measures necessary for Coffeeshop X to mitigate these risks. These measures aim to reduce the likelihood and impact of such events, ensuring that business activities can proceed smoothly and securely. The study's findings underscore the importance of a robust risk management strategy to safeguard the operations of Coffeeshop X and maintain its business continuity.